Comparative sequence analyses of the major quantitative trait locus phosphorus uptake 1 (Pup1) reveal a complex genetic structure - Heuer, Sigrid; Lu, Xiaochun; Chin, Joong Hyoun; Tanaka, Juan Pariasca; Kanamori, Hiroyuki; Matsumoto, Takashi; De Leon, Teresa; Ulat, Victor Jun; Ismail, Abdelbagi M.; Yano, Masahiro; Wissuwa, Matthias (Wiley, 2009)
The phosphorus uptake 1 (Pup1) locus was identified as a major quantitative trait locus (QTL) for tolerance of phosphorus deficiency in rice. Near‐isogenic lines with the Pup1 region from tolerant donor parent Kasalath typically show threefold higher phosphorus uptake and grain yield in phosphorus‐deficient field trials than the intolerant parent Nipponbare. In this study, we report the fine mapping of the Pup1 locus to the long arm of chromosome 12 (15.31–15.47 Mb). Genes in the region were initially identified on the basis of the Nipponbare reference genome, but did not reveal any obvious candidate genes related to phosphorus uptake. Kasalath BAC clones were therefore sequenced and revealed a 278‐kbp sequence significantly different from the syntenic regions in Nipponbare (145 kb) and in the indica reference genome of 93‐11 (742 kbp). Size differences are caused by large insertions or deletions (INDELs), and an exceptionally large number of retrotransposon and transposon‐related elements (TEs) present in all three sequences (45%–54%). About 46 kb of the Kasalath sequence did not align with the entire Nipponbare genome, and only three Nipponbare genes (fatty acid α‐dioxygenase, dirigent protein and aspartic proteinase) are highly conserved in Kasalath. Two Nipponbare genes (expressed proteins) might have evolved by at least three TE integrations in an ancestor gene that is still present in Kasalath. Several predicted Kasalath genes are novel or unknown genes that are mainly located within INDEL regions. Our results highlight the importance of sequencing QTL regions in the respective donor parent, as important genes might not be present in the current reference genomes.